2017
DOI: 10.1111/ijpp.12359
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of patients’ trust in pharmacists: empirical investigation in the United Arab Emirates

Abstract: Objectives To empirically identify the antecedents that influence patients trust in pharmacists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…Overall, the final model highlights that role awareness and pharmacist familiarity explains 38.7% of the variance in pharmacist trust. These findings reinforce 7 and extend 6 , 7 our understanding of the antecedents of pharmacist trust. Specifically, the final model revealed that pharmacist familiarity has a stronger influence than role awareness in assessments of pharmacist trust.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Overall, the final model highlights that role awareness and pharmacist familiarity explains 38.7% of the variance in pharmacist trust. These findings reinforce 7 and extend 6 , 7 our understanding of the antecedents of pharmacist trust. Specifically, the final model revealed that pharmacist familiarity has a stronger influence than role awareness in assessments of pharmacist trust.…”
Section: Discussionsupporting
confidence: 78%
“…While interpersonal trust has been explored in health care generally, empirical research focused on the various aspects of interpersonal trust within a community pharmacy context is limited. Though interpersonal trust has been measured in multiple studies, and antecedents have been modelled, 6 , 7 no study operationalized trust in the same way, making comparability of findings difficult and highlighting the need for consistent measurement. Building on Hall et al’s 1 , 11 interpersonal trust in health care context, this research presents a unidimensional and condensed measure of interpersonal trust between patient and pharmacist that is parsimonious, reliable, and valid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceived customer value further influences consumer satisfaction and consumer loyalty, with a more salient effect in pharmacy services by comparison with other service-intensive industries [ 24 ]. In addition, we also measured the level of trust in the advice received in pharmacies as a unidimensional construct [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…To increase patients' reliance in pharmacists, pharmacy organizations and governments should also work to increase patients' contentment with pharmacies and their ability to self-administer medications. [70].…”
Section: Taha Et Al (2016) -Indonesiamentioning
confidence: 99%